Web-Based Final Assignment Monitoring Information System Design - Simanjuntak, Pastima; Jayadi, Akhmad; Lase, Devi Chrisman (Tsabit Journal of Computer Science, 2025)
This study aims to design a web-based final assignment monitoring information system in the Business Administration Study Program, Malikussaleh University. This is motivated by various problems in the process of submitting and managing final assignments which are still done manually, such as administrative errors and the slow process of submitting final assignments by students. To overcome these problems, a web-based monitoring information system was developed using the CodeIgniter framework, Bootstrap, and an integrated MySQL database. This system is equipped with several main features, including monitoring student and lecturer data, recording guidance progress, managing activity schedules, and real-time notifications. The implementation results show that the system has succeeded in automating the final assignment administration process, facilitating monitoring guidance progress, and increasing the effectiveness of communication between students and supervisors. With this system, it is expected to provide a structured and efficient solution in managing final assignments.